Muslim Students Consciousness to Use Halal Cosmetic Products at Semarang City, a psychological analysis - Hayati, Mardiyan; Ahmad, Sriyono; Muthohar, Sofa (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2024)
It is important to know the awareness of Muslimah students using halal cosmetics to protect Muslim consumers in the use of cosmetic products. This study aims to describe how consciousness of Muslim students at Semarang to use halal cosmetics. Researchers used mix-method qualitative-quantitative research methods with survey techniques. Sampling was done by using cluster random sampling technique at public and religious universities in Semarang City. Data collection techniques used questionnaire on 145 female students from 7 major universities in the city of Semarang. Last analysis used religious psychology. The results of the research have shown that their level of consciousness to carry out Islamic values ​​in daily life reaches 90.3%. The relationship between religious consciousness and the use of halal products among Muslim female students from both santri and non-santri in Semarang City is very high (71%) Thus, that attitude of students is included in self-directive religious consciousness category, namely religious behavior due to personal encouragement, and not affected by the environment.